2010
DOI: 10.3109/17477160903576093
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socioeconomic factors on fitness and fatness in Spanish adolescents: The AVENA study

Abstract: Objective. This study was to examine the influence of socioeconomic status on fitness and fatness in Spanish adolescents. Subjects and Methods. A total of 1 795 adolescents (833 boys) aged 12.5–18.5 years from the AVENA study participated in this study. The following physical fitness components were assessed: muscular strength (standing long jump), speed‐agility (4 × 10 m shuttle run) and cardiorespiratory fitness (20 m shuttle run). Total and central body fat was assessed using skinfold thickness and waist ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 30 publications
7
46
4
Order By: Relevance
“…The present findings should, however, be interpreted with some caution, because we cannot rule out sample bias as an explanation (Tables II and III). Although we did not observe a clear, direct association between SES and physical fitness in children from Bogotá, as has been shown to some extent, elsewhere, 5,7,27 the present data do suggest that area-level SES may influence fitness to a greater extent than family income. This may be because this is a better indicator of local-area amenities that provide children with the opportunity to develop or maintain fitness via access to safe play areas or sporting infrastructure.…”
Section: Avena (Feeding and Assessment Of Nutritional Status Ofcontrasting
confidence: 70%
See 1 more Smart Citation
“…The present findings should, however, be interpreted with some caution, because we cannot rule out sample bias as an explanation (Tables II and III). Although we did not observe a clear, direct association between SES and physical fitness in children from Bogotá, as has been shown to some extent, elsewhere, 5,7,27 the present data do suggest that area-level SES may influence fitness to a greater extent than family income. This may be because this is a better indicator of local-area amenities that provide children with the opportunity to develop or maintain fitness via access to safe play areas or sporting infrastructure.…”
Section: Avena (Feeding and Assessment Of Nutritional Status Ofcontrasting
confidence: 70%
“…Again, these factors have not been considered specifically in previous studies of the association between SES and fitness. 5,7,27 Greater cardiorespiratory fitness in private schools may be attributable to superior facilities and students' greater rates of participation in sports and activities, which promote cardiorespiratory fitness, during and after school. Colombian public schools are mandated to provide 2 hours of weekly physical education compared with the 4-6 hours typical of private schools.…”
Section: Avena (Feeding and Assessment Of Nutritional Status Ofmentioning
confidence: 99%
“…However, different results were found in studies separately analyzing the physical fitness components [9,36]. In a state capital in the south of Brazil, adolescents (10-15 years of age) with higher socioeconomic status had better cardiorespiratory fitness levels compared to those belonging in lower socioeconomic groups [9].…”
Section: Discussionmentioning
confidence: 84%
“…"Power" is actually the application of an optimum amount of force (not maximal) and an optimal speed in order to perform an exercise [173]. The present search highlighted 2 main adopted tests for the assessment of speed, agility and coordination: the 4×10 mSRT with 9 records found [28,31,49,122,124,142,[197][198][199] and the 10×5 m sprint test with 4 records found [160,185,200,201] (Table 4). (Table 7).…”
Section: Flexibilitymentioning
confidence: 99%
“…The program is also supported by the American Alliance for Health, Physical Education, Recreation and Dance (AAHPERD). A total of 52 articles have been found that used this FTB (we do not report them in this review), while 1 article has evaluated the validity and reliability of this battery [199]. This is a 6-test battery, including Bent arm hang, Curl-up, 90 degree push-Up, modified Pull Up, Back Saver Sit and Reach, Shoulder Stretch, Trunk Lift (Table 8).…”
Section: Skill-related Componentsmentioning
confidence: 99%